Hubungan Self Compassion dengan Self-Regulation pada Pasien Diabetes Tipe 2 - Ana Fitria Nusantara; Ainul Yaqin Salam (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
Understanding psychosocial aspects, including Self-compassion, is predicted to help overcome psychological barriers in diabetic patients. This study aimed to determine the relationship between Self-compassion, self-regulation, and psychological well-being in diabetic patients—correlative descriptive research design with a cross-sectional approach. The total population was 31 diabetic patients registered as Prolanis participants at the Pajarakan Health Center, Probolinggo. Data collection was done using the Self-compassion Scale (SCS-SF) questionnaire, Self-Regulation Questionnaire (TRSQ). Data were analyzed using the SPSS Spearman Rank. The results showed that Self-compassion was mostly good for as many as 20 (64.5%), good scores dominated self-regulation by as many as 14 (45.2%) respondents. The Spearman rank bivariate test results showed a significant relationship between Self-compassion with self-regulation with p-value = 0.000 (p < 0.05) with r = 0.385. Self-compassion has essential implications in the formation of self-regulation of diabetic patients. Keywords: diabetes, Self-compassion, self-regulation.